ФОРМУВАННЯ НАВЧАЮЧИХ СУКУПНОСТЕЙ ДЛЯ СИСТЕМ ДІАГНОСТУВАННЯ ЕЛЕКТРОЕНЕРГЕТИЧНОГО ОБЛАДНАННЯ З УРАХУВАННЯМ РЕЖИМІВ ЙОГО РОБОТИ - Герцик, С.М. (Інститут електродинаміки Національної академії наук України, 2019)
Methods are proposed for the formation of diagnostic signs of the studied power equipment, which operates in different speed modes. Using the examples of studying vibrations of rolling bearings of electric power machines, it is proved that it is necessary to form spaces of diagnostic signs taking into account the operating modes of the objects under study. Obtaining the experimental data was performed using a laboratory sample of the vibrodiagnostics system of electric power equipment nodes. References 7, figures 2, table.